The Zarathustra: Exploring the Interplay of Marriage, Faith, and Social Life - Murshida Khatun; Md Amirul Islam (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2024)
This paper explores the intricate interplay between marriage, faith, and social dynamics within the framework of Zoroastrianism, commonly referred to as the Zarathustra religion, offering a succinct exposition of its historical origins and cultural significance. The aim of this study is to examine the impact of the Zarathustrianism belief system on the institution of marriage, the formation of social connections, and the development of individual and communal practices. The methodology employed in this study entails a descriptive qualitative approach that involves an extensive analysis of textual sources, anthropological studies, historical records, and data gathered from surveys conducted in 2004 and 2012. The findings of this research uncover the religious rituals associated with marriage, the influence of faith on marital relationships, and the consequences of religious teachings on social norms and customs for most worshipers of this religion who live in India, Iran, and the USA. It casts light on the complex relationships between marriage, religion, and social life within the context of the Zarathustrianism religion, offering insightful information about the real-world experiences of its adherents and the enormous relevance of these components within their community.